Natalizumab is Effective for the Treatment of Relapsing-remitting Tumefactive Multiple Sclerosis - Nakamura, Masataka (Intern Med, 2017)
We herein report the case of a 57-year-old woman presenting with a biopsy-proven tumefactive demyelinating lesion as her first clinical event. Subsequently, she displayed a relapsing-remitting course with recurrence of large demyelinating lesions exceeding 2 cm in diameter rather than the small ovoid lesions characteristic of multiple sclerosis. Administration of interferon beta did not suppress the disease activity. Finally, treatment with natalizumab, which is a humanized monoclonal antibody against the cell-adhesion molecule α4-integrin, was initiated, resulting in clinical and radiological stabilization. Our experience here suggests that natalizumab may be an effective therapeutic option for relapsing-remitting tumefactive multiple sclerosis with high disease activity.